BURST CAPACITY ANALYSIS OF MULTIPLE CIRCUMFERENTIALLY INTERACTING CORROSION DEFECTS SUBJECTED TO INTERNAL PRESSURE AND LONGITUDINAL COMPRESSIVE STRESS - YAHYA, MUHAMMAD IKHWAN (IRC, 2018)

(untitled)
In the piping system, corrosion is the natural process that will occur on the pipe wall either internally or externally. Thus, it will affect the system efficiency and produce a dangerous environment. Corrosion is the most dangerous factor in the piping system and also in others process equipment. Corrosion defect will cause fatal accident to the area such as power plant. For example, in November 2013, rupture accident of Huang-Wei pipeline happened, which caused a large quantity of oil leakage, and the oil spilled into the rainwater pipeline. Many roads and motor vehicles were dynamited in this accident. 52 people were killed, 11 people were missing. These defects will affect the thickness at a particular area of the pipe as it will be the reducing agent for the wall thickness. Thus, the percentage of pipe burst will be increased and the main concern about this project is to predict the failure pressure for the piping system. DNV-RP-F101 code and finite element analysis (FEA) simulation were used to develop the equation that can predict the failure pressure of the corroded pipe subjected to internal pressure and longitudinal compressive stress.